2020
DOI: 10.1093/tas/txaa137
|View full text |Cite
|
Sign up to set email alerts
|

The effects of high-oleic peanuts as an alternative feed ingredient on broiler performance, ileal digestibility, apparent metabolizable energy, and histology of the intestine1

Abstract: Locally grown feed ingredients of high energy and protein content, such as peanuts, maybe economically feasible alternatives to corn and soybean meal in broiler diets. Even though normal-oleic peanuts have been demonstrated to be a viable feed ingredient for poultry, few studies to date have examined the use of high-oleic peanuts (HO PN) as an alternative feed ingredient for broiler chickens. Thus, we aimed to determine the effect of feeding HO PN on broiler performance, nutrient digestibility and intestinal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…To date, minimal studies examined the effect of PNM, LSM, or their combination with or without enzyme mixture on nutrient digestibility of broilers ( Toomer et al, 2020a , Toomer et al, 2020b ). Feeding on PNM and LSM with or without enzyme mixture did not affect the digestibility coefficients of crude fibre and crude fat in broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, minimal studies examined the effect of PNM, LSM, or their combination with or without enzyme mixture on nutrient digestibility of broilers ( Toomer et al, 2020a , Toomer et al, 2020b ). Feeding on PNM and LSM with or without enzyme mixture did not affect the digestibility coefficients of crude fibre and crude fat in broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Rodriguez et al (2001) , the authors reported that dietary inclusion of LSM negatively affected amino acid digestibility. Toomer, Sanders, et al (2020) said that apparent fat and protein digestibility did not alter by dietary incorporation of 10% high-oleic PNM. The authors revealed that treated birds recorded the highest apparent metabolizable energy, suggesting improved nutrient uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Collected ileal digesta and excreta were then oven dried at 70°C for 24 h and ground through a 1-mm screen prior to analysis. Gross energy in the feed and dried excreta samples was measured as discussed in Toomer et al (2020a) using an adiabatic oxygen bomb calorimeter (IKA model C5003onnected to compressed oxygen with NESLAB Refrigerated Re-circulator CFT-25).…”
Section: Methodsmentioning
confidence: 99%
“…Laurel, PA) following AOAC 990.03 methods, then the total protein in the sample was calculated using Kjeldahl conversion factor of 6.25. Crude fat content was measured gravimetrically after Soxhlet extraction using diethyl ether as discussed in Toomer et al (2020a) .…”
Section: Methodsmentioning
confidence: 99%
“…Hence, whole unblanched (skin intact) peanuts may serve as a nutrient-rich value-added alternative feed ingredient for animal food production while reducing the production of agricultural waste by-products from the peanut industry. Thus, numerous studies have been conducted to explore the effective utilization of peanuts and/or peanut by-products within the animal feed as value-added feed components [3][4][5][6][7][8][9][10] and to enhance agricultural sustainability.…”
Section: Introductionmentioning
confidence: 99%